2014
DOI: 10.4025/actasciagron.v37i1.18181
|View full text |Cite
|
Sign up to set email alerts
|

<b>The behavior of maize hybrids generated from contrasting progenies regarding the use of nitrogen

Abstract: ABSTRACT. The purpose of this study was to evaluate the performance of maize hybrids synthesized from contrasting genotypes with regard to the use of nitrogen that were selected for their performance in topcrosses. Sixty-seven S 0:1 progenies derived from the germplasm bank of Ufla were evaluated in topcross combinations with two testers at two nitrogen levels. The six progenies with the greatest tolerance and responsiveness to nitrogen (RT) and the five with the least tolerance and responsiveness (R n T n ) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…According to Bolaños & Edmeades (1996), a yield reduction of 20 to 30% in abiotic stress conditions, compared to non-stress conditions of the same genetic set, is considered indicative of stress. Although the reduction observed in the present study was slightly lower than the recommended range, the results obtained were higher than those reported by Guedes et al (2015) and Heinz et al (2019), who observed yield decreases of only 13% and 16%, respectively.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…According to Bolaños & Edmeades (1996), a yield reduction of 20 to 30% in abiotic stress conditions, compared to non-stress conditions of the same genetic set, is considered indicative of stress. Although the reduction observed in the present study was slightly lower than the recommended range, the results obtained were higher than those reported by Guedes et al (2015) and Heinz et al (2019), who observed yield decreases of only 13% and 16%, respectively.…”
Section: Resultscontrasting
confidence: 89%
“…(CV e ) obtained under N stress were higher than those observed under conditions of high N availability for GY and PE, as shown in Table 3. This increase in CVe due to N stress is consistent with findings from other studies on corn (Bänziger et al, 1997;Santos et al, 1998;Guedes et al, 2015;Almeida et al, 2018;Torres et al, 2019) reported in the literature. One possible explanation for this difference in CV e is that in environments with a high supply of N, soil deficiencies are corrected through fertilization.…”
Section: The Coefficient Estimates Of Experimental Variationsupporting
confidence: 93%
“…Although water deficit is a complex characteristic, it must be understood for improving plant breeding (Cattivelli et al, 2008). Guedes et al (2014) indicated that for obtaining superior genotypes, the use of diverse characteristics can be a better tool. It has also been indicated for reducing costs and labor, with accurate results (Sousa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%